Acupuncture for the Treatment of Cardiovascular Diseases: A Systematic Review - Rodrigo de Lima Pimentel; Alice P. Duque; Beatriz R. Moreira; Luiz F. Rodrigues, Junior (Medical Association of Pharmacopuncture Institute, 2019)
Acupuncture, for the westerns countries, is an innovative and low-cost therapy for treatment and prevention of cardiovascular diseases (CVDs). However, most of its effects and mechanisms are poorly understood. Thus, the objective of this work was to systematically review the literature regarding the clinical effects of acupuncture for the treatment and prevention of CVDs. A search for papers published in English or Portuguese in the past 20 years was conducted at PubMed, SciELO, and PEDro databases. Clinical trials conducted on the effects of acupuncture were included in this review. Two reviewers extracted the data independently from the remaining 17 articles after screening. The most used acupoint was PC6 (10 studies, 64.7%), followed by ST36 (6 studies, 35.3%) and auricular acupoints (4 studies, 23.5%). Among the clinical applications, hypertension was the most studied CVD, with acupuncture being the most reported method among the studies (70.6%). Only three articles reported no benefit in the treatment of CVDs for the methodology used. We conclude that although several studies indicated an improvement in the response of the cardiovascular system in CVDs by acupuncture, electroacupuncture, or electrostimulation treatment, the heterogeneity of the studies does not allow a standardization of its application for each specific disease, making further studies necessary for its use to become a reality. Keywords: acupuncture, cardiovascular disease, electroacupuncture (EA), transcutaneous electrical acupoint stimulation (TEAS)